Action and resistance of monoclonal CD20 antibodies therapy in B-cell Non-Hodgkin Lymphomas. Issue 8 (September 2015) - Pérez-Callejo, D.; González-Rincón, J.; Sánchez, A.; Provencio, M.; Sánchez-Beato, M.
<x xml:space="preserve">Abstract</x> Highlights Anti-CD20 mAbs combined with chemotherapy have become the standard treatment of Non-Hodgkin Lymphomas (NHL). Mechanisms of action of this anti-CD20 mAbs in vivo are not fully understood. Binding of rituximab to CD20 is not sufficient to heal every patient with a Non-Hodgkin Lymphoma. We review the mechanisms of action and resistance of rituximab, and the efforts needed to overcome it. We also focus on new drugs targeting pathways implicated in resistance to anti-CD20 mAbs.